Physical Activity vs. Pharmacotherapy in PCOS Treatment: A relief of Clinical Evidence on Exercise and Metformine Efficacy - Bartold, Magdalena; Pohrybieniuk, Janina; Piotraszewska, Marta; Grys, Maria; Kochański, Filip; Wołk, Karolina; Skudzińska, Magda; Jaskulska, Aleksandra; Błonka, Dominika; Pietrzak, Jan (Quality in Sport, 2025)
Introduction Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age, characterized by hormonal imbalance, insulin resistance, and ovulatory dysfunction. It presents with a wide range of symptoms, including menstrual irregularities, hyperandrogenism, and metabolic disturbances, often leading to infertility and increased long-term cardiometabolic risk. Lifestyle interventions and pharmacological treatments, particularly physical activity and metformin, remain central to PCOS management. This review aims to synthesize current evidence on the comparative and complementary roles of exercise and metformin in addressing the metabolic and reproductive manifestations of PCOS. Aim of the study To Company the clinical efficacy of physical activity (exercise) and pharmacotherapy (metformin) in managing the symptoms of Polycystic Ovary Syndrome (PCOS). Materials and Methods A review of the literature collected in the PubMed database was performed to gather information found under the key words: „Polycystic Ovary Syndrome (PCOS)”, „physical activity”, „exercise”, „metformin”, „metabolic syndrome”, „fertility” and „pharmacotherapy”. Summary Managing polycystic ovary syndrome (PCOS) effectively involves both exercise and medication. Regular aerobic activity improves insulin sensitivity and reproductive health, while metformin addresses insulin resistance and metabolic issues. A combined approach of lifestyle changes and pharmacotherapy offers the best outcomes for women with PCOS.